Influence of government policies on industry development: The case of India's automotive industry - Mahipat Ranawat; Rajnish Tiwari (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2009)
The automotive industry in India has come a long way from its nascent state at the time of India's independence in 1947 to its present day dynamic form. As compared to the production of mere 4,000 vehicles in 1950, the production of the industry crossed the historic landmark of 10 million vehicles in 2006. Today, the industry produces a wide range of automobiles and auto-components catering to both the domestic as well as foreign markets. The development of the industry has been shaped by the demand on the one hand and the government interventions on the other; the influence of the latter being considerable. The evolution of India's automotive industry is identified to have occurred in four phases. In the first (1947-1965) and second phase (1966-1979), the important policies identified were related to protection, indigenisation and regulation of the industry. On the one hand, these policies helped India to build an indigenous automotive industry, while on the other it led to unsatisfactory industry performance. In the third phase (1980-1990), the single most important policy identified was the one with regard to relaxation in the means of technology acquisition. The foreign competition inducted into the industry transformed its dynamics. Lastly, in the fourth phase (1991 onwards) the liberalisation with regard to foreign investment had a significant influence on the Indian automotive industry as we see it today. This work traces the evolution of the automotive industry from its inception to present day and identifies the important policies made by the Indian government. The work also studies the influence of important policies on the development of the industry.
urn:nbn:de:gbv:830-tubdok-5600
Keywords: 650; India; Automotive; Industrial Policy; Government Policy; Government Influence